Predictors of Survival in Patients with Advanced Gastrointestinal Malignancies Admitted to the Intensive Care Unit. (5th December 2018) - Ko, Heidi; Yan, Melissa; Gupta, Rohan; Kebbel, Kayla; Maiti, Abhishek; Song, Juhee; Nates, Joseph; Overman, Michael J.
Abstract: Background: Patients with cancer have a high use of health care utilization at the end of life, which can frequently involve admissions to the intensive care unit (ICU). We sought to evaluate the predictors for outcome in patients with gastrointestinal (GI) cancer admitted to the ICU for nonsurgical conditions. Patients and Methods: The primary objective was to determine the predictors of hospital mortality. Secondary objectives included investigating the predictors of ICU mortality and hospital overall survival (OS). All patients with GI cancer admitted to the ICU at the University of Texas MD Anderson Cancer Center between November 2012 and February 2015 were retrospectively analyzed. Cancer characteristics, treatment characteristics, and Sequential Organ Failure Assessment (SOFA) scores were analyzed for their effects on survival. Results: The characteristics of the 200 patients were as follows: 64.5% male, mean age of 60 years, median SOFA score of 6.7, and tumor types of intestinal (37.5%), hepatobiliary/pancreatic (36%), and gastroesophageal (24%). The hospital mortality was 41%, and overall 6‐month mortality was 75%. In multivariate analysis, high admission SOFA score > 5, poor tumor differentiation, and duration of metastatic disease ≤7 months were associated with increased hospital mortality. For OS, high admission SOFA score > 5, poor tumor differentiation, and patients who were not on active chemotherapy because of poor performance had worse outcome. In multivariate analysis, SOFA score remained significant for OS even after excluding patients who died in the ICU. Conclusion: For patients with metastatic GI cancer admitted to the ICU, SOFA score was predictive for both acute and long‐term survival. A patient's chemotherapy treatment status was not predictive for hospital mortality but was for OS. The SOFA score should be utilized in all patients with GI cancer upon ICU admission for prognostication. Implications for Practice: Patients with cancer have a high use of health care utilization at the end of life, which can frequently involve admissions to the intensive care unit (ICU). Although there have been substantial increases in duration of survival for patients with advanced metastatic cancer, their mortality after an ICU admission remains high. GI malignancy is considered one of the top three lethal cancers estimated in 2017. Survival of critically ill patients with advanced GI cancer should be evaluated to help guide treatment planning. Abstract : This article evaluates the predictors for outcome in gastrointestinal cancer patients who were admitted to intensive care for nonsurgical conditions, focusing on predictors of survival for hospital mortality in critically ill patients with gastrointestinal cancer.